The effectiveness of pulsed electrical stimulation in the management of osteoarthritis of the knee - Fary, Robyn (Curtin University, 2010)
Osteoarthritis of the knee is a chronic disease leading to considerable burden on health. Pain, while not always present is the most prominent clinical feature and the cause of significant disability. There are a wide variety of treatment options available to patients, many with substantial side effects or contraindications for use. However, these options have modest effects at best and target symptoms rather than the disease.Pulsed electrical stimulation (PES) is an electrotherapy treatment modality using capacitively coupled, pulsed, monophasic current with a frequency of 100Hz, delivered at sub-sensory intensity. It has been reported to produce positive outcomes for pain, function and physician global assessment in short-term randomised controlled trials (four and 12 weeks) and longer term longitudinal studies. It is relatively inexpensive, non-pharmaceutical, non-invasive and has few side effects. Despite all this its use is not widespread. In addition, PES has a putative disease-modifying action through its ability to stimulate chondrocyte activity and type II collagen formation.The aim of this doctoral research was to investigate the effectiveness of PES in treating osteoarthritis of the knee by measuring pain, function, patient global assessment, quality of life and physical activity over a period of 26 weeks.In order to do this, an initial pilot study using commercially available PES equipment was conducted. The aims of this small study following three participants over 16 weeks were to investigate whether reported improvement was maintained over the longer period of time and to pilot test the materials, process and equipment being considered for a subsequent randomised controlled trial. This study provided evidence to suggest that the longer term randomised controlled trial was warranted.The next phase of this doctoral research centred around the development of the PES and placebo-PES equipment. Initial testing of the equipment that was made to replicate the parameters reported in the literature produced unacceptable adverse skin reactions. As a consequence, further consideration was given to electrical treatment parameters and a second prototype containing pulsed, asymmetrically biphasic current with a frequency of 100Hz was developed and tested.A cross-sectional study of 25 healthy adults with no contraindications to electrotherapy was undertaken to compare the rate of adverse skin reactions after using the replicated monophasic device with that after using the asymmetrically biphasic device. These rates were also compared with the rates of adverse skin reactions cited in the PES literature. Thirteen (52%) participants experienced an adverse skin reaction after using the monophasic prototype device, while one (4%) participant demonstrated an adverse skin reaction after using the biphasic prototype device. Additionally, the rate for the monophasic prototype differed significantly from the reported rates in three of the four published studies (p<0.04). These results gave strong support for the use of the biphasic current in the proposed randomised controlled trial.In order to investigate the effectiveness of PES in treating people with osteoarthritis of the knee, a double-blind, randomised, placebo-controlled, repeated measures trial was undertaken over 26 weeks. Seventy people were randomised to either the PES or placebo group. Outcome measures included pain, function, patient global assessment, quality of life, physical activity and global perceived effect. At the end of the study at 26 weeks, there was a statistically significant improvement in pain visual analogue scale (p≤0.001) in both groups. However, there was no difference between the groups (mean change difference 0.9mm; 95% confidence interval -11.7mm to 12.5mm). Similarly no differences were found between the groups in any of the other outcome variables. These results conclude that in this particular sample of people with mild to moderate symptoms and impairment, and moderate to severe radiographic osteoarthritis of the knee, PES used over 26 weeks was no better than placebo.Osteoarthritis of the knee is a chronic condition. People suffering pain and disability from the disease need to be able to make informed choices about best available treatment options. This doctoral research provides independent evidence of the effectiveness of PES. In doing so it adds to the body of evidence available to assist those with osteoarthritis and their health care providers in making treatment choices.